International Environmental Agreements When Countries Behave Morally - Thomas Eichner; Rüdiger Pethig (Center for Economic Studies and ifo Institute (CESifo), 2022)
In the standard theoretical literature on forming international environmental agreements (IEAs) countries use to be self-interested materialists and stable coalitions are small. This paper analyzes IEA games with countries that exhibit Kantian moral behavior. Countries may behave morally with respect to both emissions (reduction) and membership in an IEA. If countries are emissions Kantians or membership Kantians the outcome of the corresponding IEA games is socially optimal. To model more realistic Kantian behavior, we define an emissions [membership] moralist as a country whose welfare is the weighted average of the welfare of an emissions [membership] Kantian and a materialist. The game with emissions moralists produces stable coalitions not larger than those in the standard game with materialists. The game with membership moralists yields stable coalitions that are increasing in the membership morality. Finally, we consider countries who are moderate moralists with respect to both emissions and membership. In that encompassing IEA game the size of the coalition is increasing in the emissions morality, the membership morality, and in the weight of the membership moralist's welfare. Depending on parameter values, the grand coalition may or may not be attained if one of the moral parameter increases and tends towards one.
Keywords: C72; Q50; Q58; 330; international environmental agreement; stable coalitions; moral behavior; Kantian ethics